The Role of the Gulf Cooperation Council's Sovereign Wealth Funds in the New Era of Oil - Naser, Hanan (International Journal of Economics and Financial Issues, 2016)
Sovereign wealth funds (SWFs) are investment vehicles by which governments invest some of a nation's wealth in domestic and international financial markets. They are important for savings and stabilization economies, where long-term investments are key feature of successful SWFs' investment strategies. Successful SWFs do not seek only for financial returns, but also social returns are critically considered as they play a vital role in their countries' socioeconomic development. Considering the amount of capital accumulated in the global SWFs in general and the Gulf Cooperation Council (GCC) funds in particular, oil prices plunge has forced the GCC's to reassess income sources and spending. Precisely, extra attention has been paid for not only further investment plans, but also for developing critical strategies that aim to diversifying the GCC economies through the efficient allocation for resources and thereby provide economic development and independency. Therefore, this paper aim to analyse the current status of GCC's SWFs and provide further suggestions in the new era of oil prices to enhance their role in the region. To do so, insights from other global successful sovereign wealth funds, such that of Norway, have been considered. The main findings reveal that transparency is a key feature for SWFs growth and the gradual movement towards better practices in structure, governance, and investment behaviour. Knowledge transfers and foreign direct investment (FDI) are also significant factors for local economic growth. Keywords: Economic growth; Sovereign wealth funds, Investment, Oil prices JEL Classifications: E21, E22, G28, F65, G12, H6